Establishing the Preferential Adsorption of Anion‐Dominated Solvation Structures in the Electrolytes for High‐Energy‐Density Lithium Metal Batteries. (13th May 2021) - Xiao, Dengji; Li, Qian; Luo, Dan; Gao, Rui; Li, Zhaoqiang; Feng, Ming; Or, Tyler; Shui, Lingling; Zhou, Guofu; Wang, Xin; Chen, Zhongwei
Abstract: The practical application of Li metal batteries (LMBs) is severely hindered by the unstable solid electrolyte interface (SEI). In this work, it is revealed that the unstable SEI mainly originates from the kinetic instability of Li + ‐solvation structures in the electrolyte which can result in continuous electrolyte decomposition and nonuniform Li deposition. To address this issue, preferential adsorption of anion‐dominated solvation complexes (A‐Coms) are established by integrating preferentially adsorbed anions (NO3 − and Li2 S8 ) into the Li + ‐solvation structures. In these structures, the locations of the lowest unoccupied molecular orbital energy level shift from solvents to anions, rendering a relieved electrolyte decomposition and an anion‐derived SEI formation. Meanwhile, the anions in the A‐coms preferentially adsorb on the Li metal surfaces due to their stronger chemisorption capability toward lithium metal anodes (LMAs) compared to the solvent molecules, effectively shielding solvent molecules from parasitic reaction with LMAs. Furthermore, the anion‐derived SEI exhibits high Li‐ion conductivity and low Li atom adhesion energy, which can facilitate uniform Li deposition. Consequently, this electrolyte can enable a high Li plating/stripping Coulombic efficiency of 98.5% over 500 cycles and a stable cycling under realistic testing conditions with a high‐energy‐density of 310 W h kg −1 based on a full cell configuration. Abstract : Anion‐dominated Li + ‐solvation complexes (A‐Coms) are established in a normal salt‐concentrated (1 m ) electrolyte. In these structures, the lowest unoccupied molecular orbital energy level transfers from solvents to anions, rendering a relieved electrolyte decomposition and stable anion‐derived solid electrolyte interface formation. Furthermore, the anions in the A‐Coms preferentially adsorb on the Li metal surfaces, effectively shielding solvent molecules from parasitic reaction with lithium metal anodes.